Ambulatory percutaneous nephrolithotomy is safe and effective in patients with extended selection criteria - Hosier, Gregory William; Visram, Kashif; McGregor, Thomas; Steele, Stephen; Touma, Naji J.; Beiko, Darren (Canadian Urological Association Journal, 2021)
Introduction: Ambulatory percutaneous nephrolithotomy (PCNL) has been limited to highly selected patients. The objective of our study was to compare complication and stone-free rates after ambulatory PCNL in standard selection criteria vs. extended criteria patients. Methods: We conducted a retrospective review of prospective data on all patients who underwent ambulatory PCNL at one academic center from 2007–2018. Extended criteria patients were defined as one or more of: age >75 years, body mass index (BMI) >30 kg/ m2, American Society of Anesthesiologists (ASA) score >2, bilateral stones, solitary kidney, transplant kidney, complete staghorn calculi, stone burden >40 mm, multiple tracts, or prior nephrostomy tubes/stents. Primary outcomes were complication rates (Clavien- Dindo classification) and stone-free rates. Results: We identified 118 patients, of which 92 (78%) met extended criteria. Mean BMI was 31 kg/m2 and 45% were ASA 3 or higher. Mean sum maximum stone diameter was 24 mm. Multiple stones were present in 25%, bilateral stones in 7%, and complete staghorn stones in 4% of patients. There was no difference in complication (12% vs. 18%, p=0.56), emergency department visit (12% vs. 18%, p=0.56), or re-admission (4% vs. 5%, p=1) rates between standard and extended criteria patients, respectively. Of the complications, 85% were Clavien-Dindo grade 1. Stone-free rates were not different between standard (84%) and extended (83%) criteria patients (p=1). No extended criteria variables were associated with complications in multivariable analysis. Conclusions: Complication and stone-free rates were not different between standard and extended selection criteria patients undergoing ambulatory PCNL. This data indicates that many of the preoperative patient and stone factors that have previously been used as exclusion criteria for ambulatory PCNL are not strictly necessary.